The histopathology of acute and chronic infections of rainbow trout Salmo gairdneri Richardson with eye flukes, Diplostomum spp. - Shariff, M.; Richards, R. H.; Sommerville, Christina (Blackwell Scientific Publications, 1980)
A histopathological study was carried out on rainbow trout suffering from acute and chronic diplostomiasis. Clinical signs were few in acutely infected fish but in chronic cases fish were blind, exophthalmic and emaciated. Acute infections resulted in subcapsular cataract formation with varying capsular change. Chronically infected fish frequently showed lens dislocation, capsular rupture or duplication and the formation of Elschnig's pearls and Wedl cells. Phacogenic uveitis was seen in many fish with capsular rupture and retinal detachment frequently occurred as a sequal to vitreous detachment.